Studies on Agronomic and Genetic Potentials of the IRRDB '81 Hevea Germplasm in Vietnam - Lam, Lai Van (1995)
Studies were conducted to evaluate the agronomic potential and to investigate the genetic structure and variability of the new Hevea germplasm which had been collected from the three states of Acre, Mato Grosso and Rondonia in Brazil, South America, by the International Rubber Research and Development Board (IRRDB). A total of 1309 new Hevea germplasm clones and 32 Wickham (domesticated) clones was evaluated on agronomic performance, physiological characateristics of latex, bark anatomy and properties of rubber in two field experiments at the Rubber Research Institute of Vietnam (RRIV), Vietnam. In general, the germplasm clones were far inferior to the Wickham clones in latex productivity, and to a lesser extent, in growth. The germplasm genotypes also possessed undesirable characteristics of crown structure. Studies on physiological characteristics of latex showed that the germplasm clones were poor in the activity of latex regeneration and showed difficulty in the flow of latex. They also had anatomical characteristics of the bark unfavourable towards the productivity of latex. However, properties of rubber derived from the germplasm clones were technically acceptable. Genotypic and phenotypic coefficients of variation for yield were found very high in the germplasm population. The new germplasm had moderate to very high broad sense heritabilities (h2O) for economic characters such as yield, growth, number of latex vessel rings and plugging index. Results of the study on genetic distance showed that there was a great genetic distance between the germplasm clones and the Wickham clones. Based on genetic divergence, the germplasm could be divided into three groups in agreement with their geographical origins, namely Acre, Mato Grosso and Rondonia. For any geographical group, variability due to clones accounted for most of the variabilities for yield and growth.